Upaya Peningkatan Minat Belajar Fisika Dengan Menggunakan Metode PhET Simulation - Lastri Manulang; Jesika Elisabeth; Jesi Alexander (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
Personal potential that goes through a significant process and is one of the needs that must be met is education. As educators, teachers must be smart in utilizing existing technology to develop learning media in an effort to increase effective learning. One of the problems encountered in creating learning media is practical learning on physics material. One example is creating media using Google products and the "PhET (Physics Education Technology)" website. PhET is interactive and designed like animation to make it easier to carry out practicums, where PhET has more than 100 simulations of material used in learning. Research was carried out to find out how much skill and reasoning the students were taught using PhET media and whether there were differences between before and after being given treatment. The method used in this research is literature study, literature review with the data sources obtained. PhET is designed to help students learn independently.